The Effect of Transformational Leadership, Work Motivation, and Job Promotion on Job Satisfaction with Organizational Commitment as an Intervening Variable: Pengaruh Kepemimpinan Transformasional, Motivasi Kerja, dan Promosi Jabatan Terhadap Kepuasan Kerja dengan Komitmen Organisasi Sebagai Variabel Intervening - Anisyahfitri, Rachmania; Rizal, Asat (Universitas Muhammadiyah Sidoarjo, 2023)
This study uses a quantitative approach with a survey method. The sampling technique used simple random sampling. The population in this study amounted to 159 employees and the sample in this study were 61 employees of PT. Candi Baru Sugar Factory in Sidoarjo. Data analysis techniques used Partial Least Square (PLS) with software SmartPLS 3.0. The results of this study prove that there is an effect of transformational leadership on job satisfaction at PT. Candi Baru Sugar Factory, there is an influence of work motivation on job satisfaction at PT. Candi Baru Sugar Factory, there is an effect of promotion on job satisfaction at PT. Candi Baru Sugar Factory, there is an influence of transformational leadership on organizational commitment at PT. Candi Baru Sugar Factory, there is an influence of work motivation on organizational commitment at PT. Candi Baru Sugar Factory, there is an effect of promotion on job satisfaction at PT. Candi Baru Sugar Factory, there is an influence of organizational commitment on job satisfaction at PT. Candi Baru Sugar Factory, there is an effect of transformational leadership on job satisfaction with organizational commitment as an intervening variable at PT. Candi Baru Sugar Factory, there is an effect of work motivation on job satisfaction with organizational commitment as an intervening variable at PT. Candi Baru Sugar Factory, there is an effect of job promotion on job satisfaction with organizational commitment as an intervening variable at PT. Candi Baru Sugar Factory.